Characterising computational thinking in mathematics education: a literature-informed Delphi study. Issue 2 (4th May 2021) - Kallia, Maria; van Borkulo, Sylvia Patricia; Drijvers, Paul; Barendsen, Erik; Tolboom, Jos
ABSTRACT: Recently, computational thinking (CT) has attracted much research attention, especially within primary and secondary education settings. However, incorporating in mathematics or other disciplines is not a straightforward process and introduces many challenges concerning the way disciplines are organised and taught in school. The aim of this paper is to identify what characterises CT in mathematics education and which CT aspects can be addressed within mathematics education. First, we present a systematic literature review that identifies characteristics of CT that have been explored in mathematics education research. Second, we present the results of a Delphi study conducted to capture the collective opinion of 25 mathematics and computer science experts regarding the opportunities for addressing CT in mathematics education. The results of the Delphi study, which corroborate the findings of the literature review, highlight three important aspects of CT to be addressed in mathematics education: problem solving, cognitive processes, and transposition.